Amelia Falldorf: capstone - Falldorf, Amelia, artist (Colorado State University. Libraries, 2018)
The artist's statement: Technology itself may be, to some, nothing more than a tool with which to expedite the process of creation; one need only think of the Adobe Suite that dominates the graphics market. However, I view technology as more of a partner in creation; not exactly sentient, but certainly more complex and invested in the work than most people see on the surface. In the process of working alongside this technology, rather than simply with or through it, I find myself at an interesting place of discovery in which my work seemingly takes on a cognizance of its own, caught between the desired intentions of my own consciousness and the unconscious product of the code. Both myself and my work thrive within the confines of this partnership - while at the same time these confines help open unexplored doors to completely unseen forms of expression and entirely new ways to produce and conceptualize art. In my Graphic Design practice, I strive for a sensitive simplicity that is both instinctually familiar to a public audience while still reacting to and pushing the limits of our current creative mindset. A strong focus on typography drives my exploration of visual communication as I skirt the line of consumer interaction and my own artistic voice. However, the larger part of my passion lies with seamlessly incorporating fresh and exciting new media techniques into the time-honored Graphic Design tradition. Consumers are rewarded with a breath of fresh air when presented with 3D-modeled or procedurally generated illustrations, new forms of visual communication that lend well to the Graphic Design mindset in the unique way that they wholly capture one's attention.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design